The Influence Of Professional Ethics, Professionalism, Independence, And Experience On The Materiality Level Of Public Sector Financial Report Auditors (Auditor at KAP Djoko, Sidik, and Indra) - Arrum Safitri; Atwal Arifin (LAFADZ JAYA Publisher, 2022)
This research aims to examine the impact of professional ethics, professionalism, independence, and experience on the materiality of financial statements for This research aims to examine the impact of professional ethics, professionalism, independence, and experience on the materiality of financial statements for the public sector. The purpose of this study is to increase public confidence, which is achieved in part through evaluating financial reports by government auditors. In this research, information was collected by sending questionnaires to the accounting companies Djoko, Sidik, and Indra. sampling method using purposeful sampling Multiple regression is the method of data analysis used. data processing software, including Microsoft Excel and SPSS version 25.0. According to the findings of this research, professionalism and experience impact the amount of materialism. Professional ethics and independence have little effect on the objective world.